Higher physical activity levels are related to faecal microbiota diversity and composition in young adults - Ortiz-Alvarez, Lourdes; Xu, Huiwen; Ruiz-Campos, Samuel; Acosta, Francisco M.; Migueles, Jairo H.; Vilchez-Vargas, Ramiro; Link, Alexander; Plaza-Díaz, Julio; Gil, Angel; Labayen, Idoia; Ruiz, Jonatan R.; Martinez-Tellez, Borja (Biology of Sport, 2025)
Increasing physical activity (PA) is recognised as an efficacious approach for preventing and treating cardiometabolic diseases. Recently, the composition of microorganisms living within the gut has been proposed as an important appropriate target for treating these diseases. Whether PA is related to faecal microbiota diversity and composition in humans remains to be ascertained. Thus, we examined the association of the time spent in objectively measured PA with faecal microbiota diversity and composition in young adults. A cross-sectional study enrolled 88 young adults aged 22.0 ± 2.3 years (72.7% women), whose time spent in PA at different intensities was objectively measured with a wrist-worn accelerometer for 7 consecutive days. Faecal microbiota diversity and composition were analysed with hypervariable tag sequencing of the V3–V4 region of the 16S rRNA gene. The mean Euclidean Norm of the raw accelerations Minus One (mg) during waking time, considered as overall PA, and the time spent in vigorous PA were positively correlated with alpha diversity indexes (all rho ≥ 0.23, P ≤ 0.034). Regarding faecal microbiota composition, participants with low time spent in vigorous PA had higher relative abundance of the Gammaproteobacteria class (q = 0.021, FDR = q -value) compared to the participants with high time spent in vigorous PA, and lower relative abundance of the Porphyromonadaceae family ( q = 0.031) and the Alistipes genus ( q = 0.015) compared to the individuals with high and intermediate time spent in vigorous PA, respectively. Our results suggest that PA, especially of vigorous intensity, is related to faecal microbiota diversity and the Gammaproteobacteria class and Porphyromonadaceae family in young adults.